Perforalactones D and E, two new C-20 quassinoids with potential activity to induce lysosomal biogenesis from the twigs of Harrisonia perforata (Blanco) Merr. Issue 44 (29th October 2021) - Liu, Shuai; Zhang, Cui-Shan; Ran, Xiao-Qian; Tang, Xiao-Han; Guo, Ya-Rong; Yan, Ying; Yao, Yong-Gang; Hao, Xiao-Jiang; Luo, Rong-Can; Di, Ying-Tong
Abstract : Two new quassinoids, perforalactones D and E, from Harrisonia perforata, could promote the expression of lysosomal genes and induce lysosomal biogenesis. Abstract : Two new quassinoids (1 and 2 ) were isolated from the twigs of Harrisonia perforata (Blanco) Merr. Perforalactone E (2 ) possesses an uncommon hexacyclic 1α, 12α:5α, 13α-dicyclo-9βH-picrasane skeleton. Its structure was determined based on spectroscopic data and X-ray crystallography. Compounds 1 and 2 could significantly induce lysosomal biogenesis through transcriptional activation of lysosomal genes.